Enhanced Disease Detection of Hairy Cell Leukaemia Through Next‐Generation Sequencing Based BRAFV600E and Phased Variant Analysis - Simon Wu; Tamia Nguyen; Imogen Caldwell; Sally Hunter; Sushmitha Kannan; Camille Santos; Yan Zhuang Yap; Clarissa Wilson; Mayani Rawicki; Constantine S. Tam; Rachel Koldej; David Ritchie; et al. (eJHaem)
ABSTRACT Introduction Longitudinal disease assessment by molecular techniques is not routine in hairy cell leukaemia (HCL). Combining BRAFV600E and other genomic targets through next‐generation sequencing (NGS) with phased variant analysis is a novel approach for disease detection in this setting. Results BRAFV600E digital droplet PCR of paired peripheral blood and cell‐free DNA (cfDNA) specimens detected residual disease in 15/48 and 6/48 specimens respectively from patients with HCL. NGS testing with phased variant analysis improved disease detection in cfDNA specimens, including those with equivocal BRAFV600E results by digital droplet PCR. Conclusion Through multiple patient‐specific genomic targets to improve sensitivity, NGS may potentially improve disease detection in HCL. Trial Registration The authors have confirmed clinical trial registration is not needed for this submission